MECHANISMS FOR IMPROVING ENVIRONMENTAL COMPETENCE - Sirojiddin Barakayevich Qorayev (European Science Publishing, 2024)
The article is aimed at educating students in the field of environmental education, positively changing their attitude towards the environment and nature, preserving nature, mitigating current global environmental problems and their negative consequences, including water shortages, global climate change and its regional impact on climate and nature. In addition, students, future teachers talk about environmental competence, environmental protection.
Keywords: environmental safety, environmental competence, nature, humanity, problem, science and technology, health, healthy lifestyle, culture, education, environment.